(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the diagnostic value of brain computed tomography (CT) and CT angiography (CTA) in identifying the etiology of non-traumatic intracerebral hemorrhage in pediatric patients. Methods and subjects: A retrospective–prospective descriptive study was conducted in 48 children diagnosed with non-traumatic intracerebral hemorrhage by CT at the National Children’s Hospital. Eligible patients were aged ≤16 years. Results: A total of 48 children aged ≤16 years with non-traumatic intracerebral hemorrhage were included, with a mean age of 8.3 ± 4.7 years. The condition was more prevalent in males than females. The etiologies of non-traumatic intracerebral hemorrhage differed significantly across age groups (p < 0.001). The most common clinical manifestations were signs of increased intracranial pressure (70.8%) and impaired consciousness (54.1%). CT effectively identified hemorrhage location and severity of injury; hematoma volume ≥30 mL, midline shift ≥5 mm, cerebral edema, and brain herniation were strongly associated with poor prognosis. CTA demonstrated a sensitivity of 91.7% and a specificity of 90% compared with digital subtraction angiography (DSA) in detecting vascular causes of hemorrhage. Conclusion: Brain CT and CTA are effective diagnostic tools that provide critical information on etiology, lesion severity, and prognosis in children with non-traumatic ICH. CTA is highly valuable for screening vascular causes before performing invasive DSA.